2019
DOI: 10.1136/bcr-2019-231533
|View full text |Cite
|
Sign up to set email alerts
|

Tubercular involvement of the lateral malleolus and adjacent calcaneus: presentation of a rare case and review of the literature

Abstract: Osteoarticular tuberculosis (TB), despite being on the wane in the developed world, stays a problem of significance in the developing world. The issue is compounded by unusual presentations, inadequate diagnostic skills and limited understanding of its management. For foot infections, despite an increased awareness, many patients may be misdiagnosed, with associated treatment delays. A 19-year-old man presented with pain and swelling on lateral aspect of right ankle for 2 months. The patient had an undermined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Before beginning protracted multimodal medical therapy, prompt cross-sectional imaging and tissue diagnosis are essential; an incomplete diagnosis could result in worse outcomes; rarely is surgical intervention necessary, and it is only done to make a diagnosis (12) . Not very much different to this case, Kumar P et al reported a case of a 19-year-old man came with lateral right ankle pain and edema for two months; the skin was attacked to the underlying bone and had an undermined discharge sinus with surrounding induration; diagnosed as lateral malleolar and calcaneal TB; after receiving treatment with antitubercular medications, the patient's condition completely resolved after three years of follow-up (13) .…”
Section: Follow-up and Outcomementioning
confidence: 73%
See 1 more Smart Citation
“…Before beginning protracted multimodal medical therapy, prompt cross-sectional imaging and tissue diagnosis are essential; an incomplete diagnosis could result in worse outcomes; rarely is surgical intervention necessary, and it is only done to make a diagnosis (12) . Not very much different to this case, Kumar P et al reported a case of a 19-year-old man came with lateral right ankle pain and edema for two months; the skin was attacked to the underlying bone and had an undermined discharge sinus with surrounding induration; diagnosed as lateral malleolar and calcaneal TB; after receiving treatment with antitubercular medications, the patient's condition completely resolved after three years of follow-up (13) .…”
Section: Follow-up and Outcomementioning
confidence: 73%
“…Two weeks postoperatively, the surgical wound heal with no complication. Four weeks post-operatively ESR returned to (13). Six weeks post-operatively, she was weaned from the long walker boot and advised to start physiotherapy for the right ankle.…”
Section: Follow-up and Outcomementioning
confidence: 99%
“… 18 Of foot and ankle involvement with M. tuberculosis , the calcaneum has the highest reported incidence, probably because it is the most vascular bone of the foot, while it is continuously subjected to the stresses as it contacts the ground. 19 Once the bone or the synovium is seeded, the bacilli may progressively infect the tissues or remain dormant to be reactivated when the patient’s immunity is suppressed. 20 If the synovium is seeded first, the lesion gradually evolves to become a pannus and spreads through the articular cartilage to reach the subchondral region.…”
Section: Discussionmentioning
confidence: 99%
“…5 , 6 The duration of anti-tuberculous treatment for ankle tuberculosis in the previous reports are highly variable ranging from 6 to 18 months. 19 , 31 Prolonged chemotherapy is often justified since osteoarticular tuberculosis, predominantly being paucibacillary with dormant bacilli, hence resistant to anti-tuberculous treatment. 19 , 32 Early diagnosis is a major prognostic determinant of ankle tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation